REASONS FOR FAILURE OF EXCLUSIVE BREASTFEEDING IN CHILDREN LESS THAN SIX MONTHS OF AGE - Yaqub, Asma; Gul, Sidra (Journal of Ayub Medical College Abbottabad, 2013)
Background: Human milk is the natural food for full term infants and is the most appropriate milk for the human infants. The objective of the study was to determine the frequency of common reasons of failure of exclusive breastfeeding in children less than six months of age. Methods: It was a cross-sectional study conducted at Rawal institute of health sciences (RIHS) from March to October 2013. Three hundred and ten infant-mother pairs not receiving exclusive breastfeeding were included. Results: The mean infants’ age was 99.2±57.9 days and 185 (59.7%) were male infants. The average number of children in the family was 2.74±1.86, the mean monthly income was 16542±12761 rupees; 169 (54.5%) infants belonged to urban areas, 122 (39.3%) babies were low birth weight; 241 (77.7%) infants were born in the hospital; majority, i.e., 135 (43.5%) mothers were illiterate majority, i.e., 282 (91%) mothers were housewives. In only 2 (0.6%) babies the breast feeding was started within <1 hour after birth. Among the study group 246 (79.4%) were partially breastfed and 64 (20.6%) were completely bottle-fed, 90 (29%) were already started on complementary feeding and the mean age of starting complementary feeding was 4.54±0.783 months. The commonest reason of failure of exclusive breastfeeding was insufficient milk production in 289 (93.2%), working mother in 13 (4.2%) mothers, illness of baby in 2 (0.65%), illness of mother in 6 (1.9%) cases. Conclusion: The commonest reason of failure of exclusive breastfeeding was insufficient milk production in over 90% cases and was followed by working mother, illness of baby and illness of mother in the remaining. Keywords: breast feeding; exclusive breastfeeding; determinant